2002
DOI: 10.1097/00006123-200201000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Intracerebellar Hemorrhage: Clinicoradiological Analysis of 81 Patients

Abstract: This study describes clinicoradiological findings and prognostic factors regarding traumatic cerebellar injury. A general consensus emerged from this analysis that a conservative approach can be considered a viable, safe treatment option for noncomatose patients with intracerebellar clots measuring less than or equal to 3 cm, except when associated with other extradural or subdural posterior fossa focal lesions. Also, a general consensus was reached that surgery should be recommended for all patients with clot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
1
20
0
5
Order By: Relevance
“…This may be related to the withdrawal of care as a response to severe brain injury. This trend is also seen in other patient cohorts, for example, in traumatic brain injury [20]. Longer ICU stay in surviving surgical patients was likely due to surgical recovery time and prolonged weaning from mechanical ventilation [24].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This may be related to the withdrawal of care as a response to severe brain injury. This trend is also seen in other patient cohorts, for example, in traumatic brain injury [20]. Longer ICU stay in surviving surgical patients was likely due to surgical recovery time and prolonged weaning from mechanical ventilation [24].…”
Section: Discussionmentioning
confidence: 71%
“…This guidance has been developed largely from observational and retrospective studies, some of which supports EVD as a viable independent treatment option [19]. These interventions are dependent on institutional guidelines focusing on the degree of 4 th ventricle occlusion [20] or hematoma dimensions [2]. A strategy focussed solely on EVD may be ineffective compared to SDC in the management of PCF hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 They found that the factors for poor outcome were GCS score at admission (< 8) and a coexisting supratentorial traumatic lesions. Our patient with delayed cerebellar contusion had a good admission GCS score of 13 and relatively mild concomitant contrecoup supratentorial epidural hematoma, which may explain the good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6]8,10,13,19,21,25 The prognostic factors for cerebellar contusion have been reported to be Glasgow Coma Scale (GCS) score at admission and concomitant presence of supratentorial lesions. 4 Most of the concomitant supratentorial lesions were contralateral acute subdural hematoma and cerebral contusion. Furthermore, delayed traumatic intracerebellar hematoma has been reported previously.…”
Section: Introductionmentioning
confidence: 99%